How distinctive are ‘Gewürztraminer’ vineyard terroirs in South Tyrol for wine production? A metabolomics-based approach - Duley G; Ferretti CG; Morozova K; Longo E; Imperiale S; Ding Y; Poggesi S; Scampicchio M; Boselli E (Elsevier B.V., 2024)
Vitis vinifera L. ‘Gewürztraminer’ produces distinctive, aromatic wines that are strongly influenced by their terroir. This metabolomic study used a data-driven approach, including Principal Component Analysis (PCA) and Multifactorial Analysis (MFA), to correlate a quali-quantitative multivariate concept of terroir (including soil characteristics, and altitude) with sensory, phenolic, antioxidant, and volatile profiles of wines. The study analyzed wines from seven ‘Gewürztraminer’ vineyards, chosen to minimize the variability due to climate differences. Based on the soil data, the vineyards were clustered into two distinct groups: clay silicate (Group A) and dolomitic (Group B) soils. Group A exhibited lower levels of aromatic compounds such as linalool and higher levels of phenolic compounds such as gallocatechin than Group B. These findings indicate that even small changes in terroir within the same region can significantly impact the chemical, functional (antioxidant), and sensory properties of ‘Gewürztraminer’ wines, highlighting the importance of terroir in wine production. Statistical analyses confirmed the significance of these correlations (p < 0.05), highlighting the need for further research into the intricate relationship between terroir and wine quality.
Keywords: Authenticity; Terroir; LC-MS; GC×GC-MS; Sensory analysis; Antioxidants; Geopedology